64 Core ultra dense multicore fiber design for optical fronthaul systems - Li, Borui (2019)
To make the most of spatial efficiency, we design 64-core trench-assisted multi-core fiber with the maximum crosstalk less than -14dB/20km, which is appropriate for the optical wireless fronthaul systems with inherent MIMO function.